2014
DOI: 10.1186/1471-2296-15-73
|View full text |Cite
|
Sign up to set email alerts
|

“Doctor, please tell me it’s nothing serious”: an exploration of patients’ worrying and reassuring cognitions using stimulated recall interviews

Abstract: BackgroundMany patients who consult their GP are worried about their health, but there is little empirical data on strategies for effective reassurance. To gain a better understanding of mechanisms for effective patient reassurance, we explored cognitions underlying patients’ worries, cognitions underlying reassurance and factors supporting patients’ reassuring cognitions.MethodsIn a qualitative study, we conducted stimulated recall interviews with 21 patients of 12 different GPs shortly after their consultati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…The context-specific and goal-directed character of doctor-patient communication has also been shown in previous research [27,40,41]. The situation-specificity of reassurance has also been demonstrated in our study exploring the patients’ perspective on reassurance, which showed that what is experienced as reassuring by patients largely depends on their specific worrying cognitions [38]. …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The context-specific and goal-directed character of doctor-patient communication has also been shown in previous research [27,40,41]. The situation-specificity of reassurance has also been demonstrated in our study exploring the patients’ perspective on reassurance, which showed that what is experienced as reassuring by patients largely depends on their specific worrying cognitions [38]. …”
Section: Discussionsupporting
confidence: 84%
“…This is in line with Epstein et al who recommended that empathy should be expressed in the beginning of the consultation, as it facilitates biomedical inquiry, reassurance and action [15]. However, affective reassurance seems to directly reassure patients who worry about the impact of their complaints on their daily functioning and do not feel heard and taken seriously by others [38]. …”
Section: Discussionsupporting
confidence: 68%
“…Future research should look for additional patient and contextual characteristics which might influence patient preferences. Examples of other potentially explicatory patient variables whose impact on communication has been checked by previous studies are personality traits (extra-introversion) [44], state and trait anxiety [45], trust [46], attachment style [47], and health literacy [10,48]. Contextual characteristics could include for instance the accessibility, continuity of care, coordination with other levels of health care and comprehensiveness, which describe the quality of healthcare systems [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The SCI is based on the premise that patients with symptoms value the following: being listened to and understood; constructive explanations which make sense of their symptoms; and support in living with their symptoms [10][11][12]. It builds on the reattribution model [13] in three ways -by using more time (similar to other moderate intensity interventions [14]), by expanding the language of explanations for symptoms, specifically avoiding simple psychosomatic causal links [4,15,16], and by emphasising management of symptoms as problems in their own right with direct impacts on quality of life.…”
Section: Introductionmentioning
confidence: 99%